Natural rubber systems and climate change: Proceedings and extended abstracts from the online workshop, 23–25 June 2020 - Pinizzotto, S.; Aziz, A.; Gitz, V.; Sainte-Beuve, J.; Nair, L.; Gohet, E.; Penot, E.; Meybeck, A. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The International Rubber Study Group (IRSG), with the International Rubber Research and Development Board (IRRDB), the CGIAR research program on Forests, Trees and Agroforestry (FTA) led by CIFOR, and the French Agricultural Research Centre for International Development (CIRAD), ran an open digital workshop on natural rubber systems and climate change on 23–25 June 2020, attended by more than 500 scientists and stakeholders.